Given the matrix equation:

[tex]\[
\left[\begin{array}{ccc}
1 & 3 & 1 \\
1 & -2 & -1 \\
2 & 1 & 2
\end{array}\right]
\left[\begin{array}{l}
x \\
y \\
z
\end{array}\right]
=
\left[\begin{array}{c}
10 \\
-6 \\
10
\end{array}\right]
\][/tex]

Solve for the vector [tex]\(\left[\begin{array}{l} x \\ y \\ z \end{array}\right]\)[/tex].



Answer :

To solve the system of linear equations represented by the matrix equation:

[tex]\[ \begin{pmatrix} 1 & 3 & 1 \\ 1 & -2 & -1 \\ 2 & 1 & 2 \end{pmatrix} \begin{pmatrix} x \\ y \\ z \end{pmatrix} = \begin{pmatrix} 10 \\ -6 \\ 10 \end{pmatrix} \][/tex]

we need to find the values of [tex]\(x\)[/tex], [tex]\(y\)[/tex], and [tex]\(z\)[/tex]. Let's break it down step-by-step.

### Step 1: Write out the system of equations

From the given matrices, we can write the system of linear equations as follows:

1. [tex]\(1x + 3y + 1z = 10\)[/tex]
2. [tex]\(1x - 2y - 1z = -6\)[/tex]
3. [tex]\(2x + 1y + 2z = 10\)[/tex]

### Step 2: Use methods to solve the system

There are various methods to solve such a system (substitution, elimination, matrix methods, etc.). Here, we'll perform the solution typically found through matrix methods without delving into extensive manual calculation details.

### Step 3: Perform matrix operations

We proceed by finding the inverse of the coefficient matrix and then multiplying it by the constant vector. Practically, we solve the equation [tex]\(A \mathbf{x} = \mathbf{b}\)[/tex] by calculating [tex]\(\mathbf{x} = A^{-1} \mathbf{b}\)[/tex].

### Step 4: Interpret the solution

The solution gives us the values for [tex]\(x\)[/tex], [tex]\(y\)[/tex], and [tex]\(z\)[/tex]:

[tex]\[ (x, y, z) = (1.0, 2.0, 3.0) \][/tex]

### Solution:

Upon solving this system, we find that:

[tex]\[ x = 1.0, \quad y = 2.0, \quad z = 3.0 \][/tex]

So, the solution to the system of equations is:

[tex]\[ x = 1, \quad y = 2, \quad z = 3 \][/tex]

This solution satisfies all three original equations:

1. [tex]\(1(1) + 3(2) + 1(3) = 1 + 6 + 3 = 10\)[/tex]
2. [tex]\(1(1) - 2(2) - 1(3) = 1 - 4 - 3 = -6\)[/tex]
3. [tex]\(2(1) + 1(2) + 2(3) = 2 + 2 + 6 = 10\)[/tex]

Thus, the solution is verified to be correct.